Pengaruh Kualitas Produk, Harga, Kesadaran Merek dan Citra Merek terhadap Keputusan Pembelian (Studi pada pembeli Honda Beat di Purwokerto) - Alfandy, Riza; Alfalisyado, Alfalisyado; Endratno, Hermin; Aryoko, Yudhistira Pradhipta (Universitas Batanghari, 2024)
The purpose of this study was to test and determine the effect of product quality, price, brand awareness, as well as brand image on purchasing decisions for Honda Beat motorbikes in Purwokerto. In this study, the population was people who bought Honda Beat motorbikes in Purwokerto with a total of 100 respondents as samples. The data used is primary data, the sample is taken with the implementation of non-probability sampling with purposive sampling as the sample type, then the data is collected using a questionnaire. Quantitative research was applied in this study as a data analysis method using multiple linear regression with the use of the SPSS version 24 programme. The findings of this study reveal that simultaneously product quality, price, brand awerness and brand image have a positive and significant influence on purchasing decisions for Honda Beat motorbikes in Purwokerto city. While partially product quality, brand awareness and brand image have a positive and significant influence on purchasing decisions. But price has no influence on purchasing decisions for Honda Beat motorbikes in Purwokerto city.